How A Cold Sitz Bath Versus Infrared Therapy Can Remove the Pain of Postpartum Perineal Wounds - Girsang, Bina Melvia; Elfira, Eqlima (Jurusan Keperawatan FIKES UNSOED, 2021)
Women who suffer perineal trauma in spontaneous labor experience pain and edema as the most common problems on the first day after delivery. Impaired mobility and a limited ability to carry out daily activities will affect the mother-baby bond. The study of the cold sitz bath intervention and infrared treatment aims to find out how these interventions can overcome the pain of perineal wounds in postpartum mothers. A quasi-experimental design was used to assess both interventions for treating pain in perineal trauma at the Madina Clinic and Sundari Hospital. The sample consisted of 40 mothers, 20 in the cold sitz bath (intervention group) and 20 in the infrared therapy (control group). Pain was measured using a numerical scale from day one to day three of the postpartum period and then the data were analyzed using the paired t-test statistical test. The results of this study revealed that the cold sitz bath hydrotherapy had a significant effect in reducing pain (p = 0.004), as well as infrared therapy (0.008). Although on the third day of the postpartum period, infrared therapy did not significantly reduce the pain level; several other factors could contribute to the significant differences in pain intensity reduction such as comfort, convenience, and the economic value of the intervention.Â